Uterovesical migration of copper-containing intrauterine device complicated by bladder stone formation - Ayodeji Sylvester Adeyanju; Jamiu Adelani Ogunsola; Gbolahan Oladele Obajimi (Wolters Kluwer Medknow Publications, 2023)
Copper-containing intrauterine device (IUD) is a common method of contraception with a low failure rate and high acceptability. However, complications could follow its use including expulsion and migration of the device out of the uterus. When migration occurs, the device could pierce other structures in the pelvis such as the rectum, sigmoid colon, small bowel, or urinary bladder. The pattern of the patient's complaints will guide the clinician on the possible organ involved and the manner of care. This case report presents a 44-year-old woman with IUD migration into the urinary bladder with resulting stone formation. She presented with pelvic pain and hematuria. Following ancillary investigations, she had laparotomy and removal of the IUD along with bladder stones. She had a satisfactory recovery after the surgery and had a complete resolution of all her preoperative symptoms.